Impact of an innovative equipment to monitor and control salt usage during cooking at home on salt intake and blood pressure: Randomized controlled trial iMC SALT - Santos, T. (2022)
(1) Background: Excessive salt consumption is associated with an increased risk of hypertension and cardiovascular disease, and it is essential to reduce it to the level recommended by the World Health Organization (<5 g/day). The main objective of this study is to verify the impact of an intervention, which used the Salt Control H equipment to reducing salt consumption; (2) Methods: The study was an 8-week randomized control trial with 114 workers from a public university. The intervention group (n = 57) used the equipment to monitor and control the use of salt during cooking (Salt Control H) at home for 8 weeks. The primary outcome was 24 h urinary sodium excretion as a proxy of salt intake. Secondary outcomes included changes in 24 h urinary potassium excretion, sodium to potassium ratio (Na:K), and blood pressure. (3) Results: There was a decrease in sodium intake after the intervention but with no statistical significance. When analyzing the results by sex and hypertension status, there was a reduction in sodium (1009 (1876 to 142), p = 0.025) and in Na:K ratio (0.9 (1.5 to 0.3), p = 0.007) in hypertensive men in the intervention group. (4) Conclusions: Interventions with dosage equipment can be valid approaches in individual salt reduction strategies, especially in hypertensive men.